1989
DOI: 10.1507/endocrj1954.36.595
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Norepinephrine Secretion by Dopamine in Children with Neuroblastoma. Evidence for Precursor Inhibition in Catecholamine Pathway.

Abstract: To elucidate catecholamine (CA) secretory dynamics in neuroblastoma,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Interestingly, Sato et al (41) found that endogenous dopamine overload in neuroblastoma inhibits NE production. The main blockade in the catecholamine pathway may be where dopamine is converted to NE.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Sato et al (41) found that endogenous dopamine overload in neuroblastoma inhibits NE production. The main blockade in the catecholamine pathway may be where dopamine is converted to NE.…”
Section: Discussionmentioning
confidence: 99%